Information Systems in Sustainable Hospitality and the Creation of Business Value - Nikoletta Klada; Asterios Stroumpoulis; Sotirios Varelas; Nicolaos Georgopoulos (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2023)
The primary study areas of this research are Information Systems, Sustainable Development and Hospitality Industry. During the last few years, many surveys have examined the connection of the above concepts and how they could lead to business performance, aiming for a competitive advantage and economies of scale. There is a gap in the international literature review regarding the above meanings and the business value. So, the main goal of this research is to find this gap and propose a conceptual framework for future research. The methodology used in this paper is based on a literature review, which tries to find the gap in the international literature and understand the concepts under examination. The main finding of this research is the development of a conceptual framework, which explains how the sustainability and the resources of Information Technology could lead to the creation of business value. Finally, hotel managers and companies could benefit from this added value and strengthen their position inside their task environment.
Keywords: M15; Z32; 330; Tourism Industry; Sustainable Development; Information Systems